Direction de l_Elevage et de l_Agriculture - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
Direction de l_Elevage et de l_Agriculture
Keywords: Pan-African Control of Epizootics (PACE)